2004
DOI: 10.1111/j.1600-0463.2004.apm1120304.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilocular cystic renal cell carcinoma: a clinicopathological, immuno‐ and lectin histochemical study of nine cases

Abstract: Multilocular cystic renal cell carcinoma (MCRCC) is an uncommon variant of renal neoplasm and its histogenesis is unclear. The aim of this study was to use immuno- and lectin histochemistry to delineate histochemical patterns which might indicate the histogenetic origin of MCRCC from a particular part or parts of the nephron. We present our experience with nine cases of MCRCC. Fifteen cases of renal cell carcinoma with cystic degeneration (RCC-CD) were selected for comparison with MCRCC. We carried out clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recently, Imura et al carried out a detailed immunohistochemical analysis of multilocular cystic RCC cases [7]. They found that in a high proportion of cases, multilocular cystic RCC reacted strongly with the distal nephron markers, but none reacted preferentially with proximal nephron markers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Imura et al carried out a detailed immunohistochemical analysis of multilocular cystic RCC cases [7]. They found that in a high proportion of cases, multilocular cystic RCC reacted strongly with the distal nephron markers, but none reacted preferentially with proximal nephron markers.…”
Section: Discussionmentioning
confidence: 99%
“…3) Septas should contain clear cell groups [6,7]. Although most RCCs originate from proximal tubules, a detailed immunohistochemical study performed by Imura et al has shown that MCRCC originates from distal tubules [8]. However, MCRCC's pathology still has not been completely illuminated [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to its particular biological property of recognizing L-fucosyl oligosaccharides present in glycoprotein and glycolipid receptors on cells, LTA has been used as a tool in various biochemical studies: (i) in the characterization of antigens and insect cells (Thomas and Surolia, 2000;Napier et al, 1974;Butters and Hughes, 1978) (ii) in examinations of surface saccharide composition in different cells (Mayliepfenninger and Jamieson, 1979;Gurd, 1979) and mainly (iii) in lectin histochemistry of malignant cells for the purpose of investigating anomalous membrane oligosaccharides and differentiating carcinomas (Raedler et al, 1983;Koch et al, 1983;Miettinen et al, 1983;Walker, 1984;Ulrich et al, 1985;Davidsson et al, 1987;Griffiths and Stephenson, 1988;Raju and Lee, 1988;Finne et al, 1989;Imura et al, 2004;Turner et al, 1995).…”
Section: Introductionmentioning
confidence: 99%